CHALLENGES IN DATA SHARING: COPYRIGHT RELATED ANOMIE - Monteiro, Elizabete Cristina de Souza de Aguiar [UNESP] (2023)
Cooperation and concerted work among the various stakeholders in the science communication cycle are crucial for effective data sharing and to enable data to be located and reused. Anomie, a term here associated with the lack of clarity of information, norms, and guidelines, the loss of normative references, the disregard for rules, or the denial of morals, is a barrier to such sharing. Copyright aspects are prevalent in the data publishers' guidelines for better reuse and citation of authors, and run through several topics. The objective was to present research on evidence that contributes to the understanding of how the state of anomie regarding copyright can inhibit data sharing. It was used the documentary, exploratory research and the Content Analysis method with framework that considers the institutional and individual dimensions. The results indicated that the researchers have little clarity about the laws and regulations, which generates an imbalance between institutional goals and the means to achieve them, including the noncompliance with guidelines. It is concluded that there are guidelines on both moral and patrimonial copyrights, however, elements were identified that point to a state of anomie related to such guidelines.